Pengaruh Promosi Kesehatan menggunakan Leaflet terhadap Persepsi Remaja Putri tentang Seks Pranikah di SMAN 2 Cibeber Kabupaten Lebak-Banten - Yenny Aulya; Jenny Anna Siauta; Fitri Rizki Pebriant; Febry Mutiariami Dahlan (Universitas Baiturrahim, 2022)
Adolescence in the 10-19 year age range will experience physical growth and maturity of reproductive organ functions, plus emotional changes in adolescents will also become more aggressive and easy to react to stimuli. The prevalence of adolescents who have premarital sex was 41%, and this figure shows an increase from year to year. The existing IDHS survey shows that the prevalence of adolescents who have premarital sex is 4.5% for men and 0.7% for women. To determine the effect of health promotion using leaflets on adolescent girls’ perceptions of premarital sex at SMAN 2 Cibeber, Lebak-Banten Regency. This study was a Quasi-Experiment with One group pre test post test design. The sample was class XI students which consisted of 35 people. The sampling technique used was total sampling. Bivariate univariate data analysis using paired t test non parametric test. The average value of the perception of adolescent girls about premarital sex before health promotion intervention was 37.65 and after health promotion intervention was increased to 52.94. The results of bivariate analysis using paired t test showed that p value 0.000 <0.05, there was a significant effect of health promotion on adolescents' perceptions of premarital sex. There was a significant effect in providing health promotion using leaflets on adolescent perceptions about the dangers of premarital sex. It is expected that adolescent grils after being given health promotion the dangers of premarital sex can prevent it.